LINGUOCULTURAL ASPECT IN THE CREATION OF WIZARD WORLD BY J.K. ROWLING - Dzhalalova Regina Anvarovna (Innovate Conferences, 2025)
One linguistic and cultural aspect in the creation of the Wizarding World by J.K. Rowling is the use of a unique and distinct magical language, such as spells, incantations, and magical creatures' names. Rowling created a whole new vocabulary for the wizarding world, drawing inspiration from Latin, Greek, and other languages to give her magical language a sense of depth and authenticity.Another aspect is the incorporation of various cultural references and traditions into the wizarding world. Rowling drew on British folklore, mythology, and history to create a rich and immersive magical world that feels familiar yet fantastical. The Hogwarts School of Witchcraft and Wizardry, for example, is reminiscent of traditional British boarding schools, but with a magical twist.
Keywords: cultural influence, meta-semantic analysis, fiction, metalinguistic context language, neologisms, corpus analysis, linguocultural aspect.